(untitled) (Journal of Comparative & International Higher Education, 2022)
This article discusses lessons learned from the development and execution of F&M in Shanghai, a hybrid residential-remote program created for Franklin and Marshall College’s first-year Chinese students in Fall 2020. The F&M Office of International Programs worked with the Institute for Study Abroad (IFSA) to develop the residential portion of the program, and coordinated the curriculum and remote engagement framework. F&M in Shanghai represented an opportunity to craft a constructive environment for first-year Chinese students by intentionally considering and meeting their specific needs. Utilizing creative, well-designed pedagogy, thoughtful programming, and a multipronged approach to student support, we were able to operate the program with great success. Assessments of F&M in Shanghai resulted in a great deal of data, and some results we observed run counter to received wisdom. This article discusses how these results suggest avenues for future research.